Interdisciplinary Working Methods: Reflections Based on Technology-Enhanced Learning (TEL) - Scanlon, Eileen; Anastopoulou, Stamatina; Conole, Grainne; Twiner, Alison (Frontiers in Education, 2019)
In this paper, we discuss the nature of interdisciplinarity and in particular the ways that interdisciplinary working is enacted in TEL Research. Following a design-based research approach, a common TEL methodological approach, we identified how interdisciplinarity facilitated the research team to address a wicked problem, fostered dialogue between researchers in different disciplines and stakeholders in the research through the lifetime of the project and facilitated the creation of new meanings. Focusing on the Personal Inquiry Project (PI) team, interdisciplinary working methods are explored through examining two boundary objects namely the PI octagon and the concept of scenario, that provide windows of how interdisciplinary understanding evolves through time and among different stakeholders. These boundary objects, even though they had different importance within the project, illustrate the team’s emergent and shared understanding while maintaining flexibility through a rapid iterative process. We discuss how a shared understanding was facilitated through active involvement of different disciplinary teams and consensus was built and refined in the light of emerging findings. Interviews with researchers on the project and the Advisory Board and on our own reflections on work practices illustrate key themes, i.e. the salience of boundary objects in the design process, the development of a common language, and the importance of a shared vision. We conclude with a set of requirements for progress in interdisciplinary working and comment on our view of good practice in fostering interdisciplinarity along with an outline of what we see as the remaining challenges.